Composition and Density of Marine Debris In the Mangrove Area of Pongkar Village,Tebing District, Karimun Regency, Riau Islands Province - Helmi Abdullah Prabowo; Adriman Adriman; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTMarine debris is a type of pollutant that commonly found in the mangrove ecosystems. This spurpose of this study was to determine the composition and density of marine debris in the mangrove ecosystem in Pongkar Village. Sample was carried out in July - August 2020. The method used is the survey method. Sampling was carried out three times (once/2 weeks) at 3 observation stations, namely S1 (ecotourism area), S2 (natural mangrove forest) and S3 (port area and residential area). Marine debris was collected from 3 plots (10 x 10 m) placed along the transect line. The types of marine debris found in the mangrove ecosystem consist of plastic, glass, rubber, cloth, styrofoam, nets, cans, wood, steel and paper. Marine density based on the characteristics of debris are: megadebris (0.01 - 0.04 items/m2; 4.61 - 34.67 grams/m2), macrodebris (1.43 - 4.75 items/m2; 249.19 - 724.53 gram/m2), mesodebris (0.79 - 2.20 items/m2; 1.54 - 3.23 gram/m2). The most common marine debris found were plastics (69.27%) and styrofoams (15.65%).Keywords:Pongkar Village, Mangrove Area and Marine Debris